HUBUNGAN TINGKAT PENGETAHUAN DAN MOTIVASI IBU TENTANG PEMBERIAN MP-ASIDENGAN STATUS GIZI BAYI UMUR 6-12 BULAN DI WILAYAH KERJA PUSKESMAS GUNUNG MEDAN DHARMASRAYA - Rida Suriani; Yepni Nensi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Nutritional status is one determinant of the quality of human resources, malnutrition will result in the failure of physical growth and intellectual development and the immune system is lowered resulting in increased morbidity and mortality. The aim of this study was to determine the relationship between mother's knowledge and motivation regarding the provision of complementary foods with nutritional status of infants 6-2 months in Publich Health Centre Gunung Medan , Dharmasraya regency in 2025. This research is an analytic survey with cross sectional study design, conducted on July 10 until July 16, 2015, population of all mothers with babies aged 6-12 months as many as 53 people, using a sample of the total sampling as many as 53 people. Collecting data by questionnaires, data processing techniques ranging from editing, coding, entry, and cleaning. By univariate and bivariate analyzes. Results of research for the poor nutritional status (17%), which has a low knowledge (47.2%), and who have low motivation (47.2%). There is a relationship between knowledge and motivation with the nutritional status of infants using-Square test with p value 0.009. There is a relationship between the level of knowledge of mothers about complementary feeding and nutritional status of infants. And there is a relationship between maternal motivation about the weaning food with nutritional status of infants at-Square test with p value 0.009. Based on the research results, it is expected to cooperate with the efforts of the health center health, that the importance of attention to the provision of breast milk and infant health so that they will not be malnourished. Increasing the level of knowledge and motivation so that mothers will not have a wrong view of the provision of complementary feeding.Keywords: Infant Nutritional Status, Knowledge Level, Motivation